In Silico Study of Compounds in Noni (Morinda citrifolia L.) against Main-Protease in SARS-CoV-2 - Lestyawan, Samuel; Fakhirah, Maitsa Alya; Prasetiawati, Riska; Anggraeni, Diyani Sovia; Muchtaridi, Muchtaridi (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
Coronavirus Disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), is a contagious illness transmitted from person to person. The main protease (Mpro) of SARS-CoV-2 is a promising target for therapeutic intervention. Noni (Morinda citrifolia L.), a plant commonly used in traditional medicine in Indonesia for treating COVID-19, has been investigated for its potential anti-SARS-CoV-2 compounds. However, the specific bioactive compounds targeting SARS-CoV-2 remain unidentified. This study aimed to identify and predict the activity of compounds in Noni against Mpro through pharmacophore modeling, molecular docking, drug-likeness, and pharmacokinetic analysis using LigandScout®, Discovery Studio Visualizer®, AutoDock®, SwissADME, Pre-ADMET, and Toxtree®. Among the 40 compounds analyzed, quercetin emerged as the most promising candidate, with a pharmacophore fit score of 41.05, a binding energy (ΔG) of -7.79 kcal/mol, and interactions with amino acid residues GLY143A and MET165A, similar to the native ligand. These findings suggest that quercetin from M. citrifolia has the potential to be developed as a novel anti-SARS-CoV-2 therapeutic agent.